Assessment of Lassa fever reporting among healthcare workers in a Southwest state, Nigeria - Adewale Moses Adejugbagbe; David Dele Sunday; Ayokunle Oluwafiyifunmi Orimolade; Olawumi Feyisike Johnson; Stephen Fagbemi; Elvis Efe Isere; Aderonke Fagbemi (Discover Public Health)
Abstract Background Delayed and non-reporting of suspected cases of Lassa fever (LF) by health workers has been linked to large scale outbreaks, resulting in high morbidity and mortality rates in Nigeria. This persists despite the government’s reactionary measures aimed at addressing surveillance gaps for LF. We assessed the factors influencing the reporting practices of LF among health workers. Methods A descriptive cross-sectional study was conducted among 219 healthcare workers in Ondo State, Nigeria in June 2023. A pre-tested semi-structured questionnaire was administered to participants to assess their knowledge of Lassa fever, attitudes towards reporting notifiable diseases and practices for reporting suspected cases of LF. Data were analysed using frequency, proportions, the Chi-Square test and binary logistic regression with statistically significance set at p < 0.005. Results A total of 214 participants were assessed. Overall, 145 (67.8%) demonstrated good knowledge of Lassa fever, and 182 (85.0%) exhibited a positive attitude towards reporting notifiable diseases. More than half (126; 58.9%) reported at least one LF case in the past year. Significant predictors of LF reporting included working in a tertiary health facility (AOR = 2.35, CI = 1.09–5.03) and a primary health facility (AOR = 3.4, CI = 1.54–7.60), having received training on LF reporting (AOR = 3.1; 95% CI = 1.63–5.99), and possessing more than 10 years of experience as a health worker (AOR = 2.45; 95% CI: 1.20–5.02). Conclusion The findings suggest that there is a strong understanding and positive attitudes toward reporting Lassa fever; however, gaps persist in actual reporting practices. Strengthening training programs and surveillance systems, particularly in lower-tier facilities, is essential for improving reporting compliance and enhancing early detection.